Characterization of the proline‐utilization pathway in Mycobacterium tuberculosis through structural and functional studies. (1st April 2014) - Lagautriere, Thomas; Bashiri, Ghader; Paterson, Neil G.; Berney, Michael; Cook, Gregory M.; Baker, Edward N.
<x xml:space="preserve">Abstract</x> The proline‐utilization pathway in Mycobacterium tuberculosis (Mtb) has recently been identified as an important factor in Mtb persistence in vivo, suggesting that this pathway could be a valuable therapeutic target against tuberculosis (TB). In Mtb, two distinct enzymes perform the conversion of proline into glutamate: the first step is the oxidation of proline into Δ1‐pyrroline‐5‐carboxylic acid (P5C) by the flavoenzyme proline dehydrogenase (PruB), and the second reaction involves converting the tautomeric form of P5C (glutamate‐γ‐semialdehyde) into glutamate using the NAD+‐dependent Δ1‐pyrroline‐5‐carboxylic dehydrogenase (PruA). Here, the three‐dimensional structures of Mtb‐PruA, determined by X‐ray crystallography, in the apo state and in complex with NAD+ are described at 2.5 and 2.1 Å resolution, respectively. The structure reveals a conserved NAD+‐binding mode, common to other related enzymes. Species‐specific conformational differences in the active site, however, linked to changes in the dimer interface, suggest possibilities for selective inhibition of Mtb‐PruA despite its reasonably high sequence identity to other PruA enzymes. Using recombinant PruA and PruB, the proline‐utilization pathway in Mtb has also been reconstituted in vitro. Functional validation using a novel NMR approach has demonstrated that the PruA and PruB enzymes are together sufficient to convert proline to glutamate, the first such demonstration for monofunctional proline‐utilization enzymes.